EFFECT OF VARIOUS INORGANIC MICRO-NUTRIENTS ON GROWTH, BIOMASS AND HYDROCARBON YIELD OF EUPHORBIA LATHYRIS L. A HYDROCARBON YIELDING PLANT : Life Science-Botany - GARG, JOLLY; KUMAR, ASHWANI (International Journal of Life Science and Pharma Research, 2012)
Energy security is one of the most pressing challenges of the 21st century. A shift to next-generational fuels and increased use of renewable source of energy are increasingly being considered as viable options. Euphorbia lathyris L. is one of the most-suitable species that falls into the category of hydrocarbon yielding plants. This plant is suitable to grow in arid and semiarid climate. Fertilizer application plays a major role in the universal need to increase in agricultural production. Different mineral nutrients like boron (boric acid), copper (copper sulphate), iron (ferrous sulphate), magnesium (magnesium sulphate), manganese (manganous sulphate), molybdenum (ammonium molybdate) and zinc (zinc sulphate), were sprayed over the plants. There was an increase in the Hexane Extractables, Methanol Extractables and total extractable (Hexane Extractables and Methanol Extractables) at Mn, Zn, Fe, Cu, Mo, Mg and B in decreasing order over the control.